2010
DOI: 10.1007/s10620-010-1249-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Prognostic Significance of Minimal Hepatic Encephalopathy in Patients with Cirrhosis of Liver

Abstract: Psychometric hepatic encephalopathy score is a useful tool for the diagnosis of minimal hepatic encephalopathy in an outpatient setting. Both psychometric hepatic encephalopathy score and Child-Turcotte-Pugh score have prognostic value on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
151
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 177 publications
(170 citation statements)
references
References 39 publications
16
151
2
1
Order By: Relevance
“…7,10,12,[16][17][18] MHE predicts the development of overt HE and also adversely affects survival as shown by several studies. 7,10,18,[84][85][86][87] Das et al 10 studied the progression of MHE to overt HE in relation to severity of liver dysfunction and found that overt HE were more frequent in patients with MHE and Child-Turcotte-Pugh (CTP) score >6. Hartmann et al 7 found that survival was determined only by CTP score irrespective of presence or absence of MHE.…”
Section: Natural History and Survival In Minimal Hepatic Encephalopathymentioning
confidence: 92%
See 1 more Smart Citation
“…7,10,12,[16][17][18] MHE predicts the development of overt HE and also adversely affects survival as shown by several studies. 7,10,18,[84][85][86][87] Das et al 10 studied the progression of MHE to overt HE in relation to severity of liver dysfunction and found that overt HE were more frequent in patients with MHE and Child-Turcotte-Pugh (CTP) score >6. Hartmann et al 7 found that survival was determined only by CTP score irrespective of presence or absence of MHE.…”
Section: Natural History and Survival In Minimal Hepatic Encephalopathymentioning
confidence: 92%
“…16 Prevalence of MHE increases with increasing severity of liver dysfunction 2,7,10,[16][17][18][19] and is not affected by etiology of cirrhosis once patients with recent alcohol intake were excluded.…”
Section: Epidemiologymentioning
confidence: 99%
“…25 The clinical significance of PHES has been evaluated in a large number of healthy volunteers and patients with MHE. 9 …”
Section: Psychometric Hepatic Encephalopathy Scorementioning
confidence: 99%
“…3,4 Early detection of MHE is clinically relevant for several reasons. Minimal hepatic encephalopathy impairs daily functioning and health-related quality of life (HRQOL), 5,6 it predicts the development of overt HE, 7,8 it is associated with poor prognosis, 9,10 and these patients experience higher rates of accidents, driving problems, and falls. [11][12][13][14] Furthermore, treatment with lactulose or rifaximin improves cognitive functions as well as HRQOL and driving simulator performance in these patients.…”
mentioning
confidence: 99%
“…They did not undergo PHES because PHES has earlier been validated in Indian population and we used the cut-off for the PHES determined previously. 14 …”
Section: Controlsmentioning
confidence: 99%